2023
DOI: 10.3390/polym15102276
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Open-Hole Strength and Toughness of Sandwich Carbon-Kevlar Woven Composite Laminates

Abstract: Fiber-reinforced plastic composites are sensitive to holes, as they cut the main load-carrying member in the composite (fibers) and they induce out-of-plane stresses. In this study, we demonstrated notch sensitivity enhancement in a hybrid carbon/epoxy (CFRP) composite with a Kevlar core sandwich compared to monotonic CFRP and Kevlar composites. Open-hole tensile samples were cut using waterjet cutting at different width to diameter ratios and tested under tensile loading. We performed an open-hole tension (OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In addition, they also found that the greater the cutout area, the lower the critical buckling load. 45 The findings presented by Khan et al 46 indicate that the hybrid laminate demonstrates reduced sensitivity to notches compared to CFRP and KFRP laminates. This is attributed to a slower decrease in strength with increasing hole size.…”
Section: Structural Analysismentioning
confidence: 96%
“…In addition, they also found that the greater the cutout area, the lower the critical buckling load. 45 The findings presented by Khan et al 46 indicate that the hybrid laminate demonstrates reduced sensitivity to notches compared to CFRP and KFRP laminates. This is attributed to a slower decrease in strength with increasing hole size.…”
Section: Structural Analysismentioning
confidence: 96%